Essential programming for the technical artist - Roda, Chris (Boca Raton, FL : CRC Press, 2024)
"This book is based on a successful curriculum designed to elevate technical artists, with no programming experience, up to essential programming competency as quickly as possible. Instead of abstract, theoretical problems, the curriculum employs familiar applications encountered in real production environments to demonstrated each lesson. Written with artists in mind, the book introduces novice programmers to the advantageous world of Python programming with relevant and familiar examples. Any digital artists, (not just technical artists), will find this book helpful in assisting with day-to-day production activities. Concentration upon subjects relevant to the creation of computer graphic assets, this book introdu9ces: Python basics, functions, data types, object-oriented programming, exception handling, file processing. graphical user interface creation, PEP 8 standards, and regular expressions. Programming within the SideFX Houdini 3D animation software provides a familiar environment for artists to create and experiment with the covered Python topics'--
Keywords: Python (Computer program language).; Computer art -- Technique